Balanced/Unbalanced Voltage Sag Ride-Through in VSI-Fed Induction Motor Drive Used for Constant Speed Application - Rao Y.T.; Bussa V.K.; Reddy B.; Yalla N. (My University, 2025)
Sag and swell (balanced/unbalanced) are more common phenomena in the utility grid due to symmetrical/unsymmetrical faults in the grid. As most of the industrial drives are connected to the utility grid, they should be able to operate in continuous running conditions without tripping during these short voltage sags. In conventional methods, kinetic energy stored will be used to maintain the dc-link of the inverter to its rated voltage for a smooth ride through during these power interrupts. However, during certain critical applications, it is required to maintain the constant speed throughout its operation which is not possible with the conventional method. To overcome these issues, in this article, new methods have been suggested for both balanced and unbalanced voltage sags. Developed algorithms have been simulated (using MATLAB/Simulink) on indirect rotor flux-oriented vector control induction motor drive, and the performance is found to be satisfactory. © 2023 IEEE.